Mechanism of mind - De Bono Edward (England, 1983)
In this fascinating and provocative book,, Dr de Bono builds up a picture of a 'special memory- surface' , which might resemble the brain in its selection, processing and rejection of information. with simple analogies he illustrates the mind's tendency to create and consolidate rigid patterns, to build myths, to polarize and divide, and divide, and then relates these mechanisms to the various modes of thinking- natural, logical, mathematical and lateral.
Keywords: Congnition